Medication errors during simulated paediatric resuscitations: a prospective, observational human reliability analysis - Appelbaum,N; Clarke,J; Feather,C; Franklin,BD; Sinha,R; Pratt,P; Maconochie,I; Darzi,A (2019)
Abstract Introduction Medication errors during paediatric resuscitation are thought to be common. However, there is little evidence about the individual process steps that contribute to such medication errors in this context. Objectives To describe the incidence, nature and severity of medication errors in simulated paediatric resuscitations, and to employ human reliability analysis to understand the contributory role of individual process step discrepancies to these errors. Methods We conducted a prospective observational study of simulated resuscitations subject to video micro-analysis, identification of medication errors, severity assessment and human reliability analysis in a large English teaching hospital. Fifteen resuscitation teams of two doctors and two nurses each conducted one of two simulated paediatric resuscitation scenarios. Results At least one medication error was observed in every simulated case, and a large magnitude or clinically significant error in 11 of 15 cases. Medication errors were observed in 29% of 180 simulated medication administrations, 40% of which considered to be moderate or severe. These errors were the result of 884 observed discrepancies at a number of steps in the drug ordering, preparation and administration stages of medication use, 8% of which made a major contribution to a resultant medi